Bibliometrics Analysis Using Vosviewer and Publish or Perish: Trends and Visualization of Soft Computing Research in Natural Language Processing (using Crossref data) - Khoir, Mochamad Thoriq; Huda, Ednan Nauzal; Suhartono (Yayasan Amanah Putra Mandiri, 2024)
The background of this research is the significant increase in the number of scientific publications related to the use of soft computing in natural language processing (NLP) in recent years. As bibliometric data becomes increasingly complex, an effective tool is needed to map and analyze this data. This study aims to analyze and demonstrate the steps of bibliometric data analysis using VOSViewer comprehensively and systematically. The method used in this research involves conducting bibliometric analysis to generate visualizations of collaboration network maps and collaboration density maps. The analysis was conducted on a total of 1000 documents obtained on the specified topic for the period 2019-2023. The results of this research can be visualized with a network map, it can be seen that the research development map in NLP is divided into 5 clusters. Cluster One consists of 8 topics, Cluster Two consists of 6 topics, Cluster Three consists of 4 topics, Cluster Four consists of 3 topics, and Cluster Five consists of 3 topics. The research conclusion shows that VOSViewer can be used to provide recommendations in data analysis results. This study provides a comprehensive and systematic guide for new users of VOSViewer to conduct bibliometric data analysis and effectively present the visualization of research developments in the field of NLP.